Adaptive Strategies for the Elderly in Inhibiting Irrelevant and Conflict No-Go Trials while Performing the Go/No-Go Task - Hsieh, Shulan; Wu, Mengyao; Tang, Chien-Hui (Frontiers in Aging Neuroscience, 2016)
This study aimed to differentiate whether or not older adults are more prone to distraction or conflict, as induced by irrelevant and conflict no-go stimuli (irNOGO and cfNOGO), respectively. This study also aimed to determine whether or not older adults would devote more effort to withholding a no-go trial in the higher-control demand condition (20% no-go trials’ probability) as compared to the lower-control demand condition (50% and 80% no-go trials’ probability). A total of 96 individuals were recruited, and each of the three no-go trials’ probability conditions included 32 participants (16 younger adults and 16 older adults). Both behavioral and event-related potential (ERP) data were measured. The behavioral results showed that the older adults performed more poorly than the younger adults for the go trials, as reflected by slower reaction times and higher numbers of omission errors in the go trials. In contrast, in the no-go trials, the older adults counter-intuitively exhibited similar behavioral performance (i.e., equivalent commission errors) as compared to the younger adults. The ERP data further showed that the older adults (but not the younger adults) exhibited larger P3 peak amplitudes for the irNOGO than cfNOGO trials. Yet, on the other hand, the older adults performed more poorly (i.e., had more commission errors) in the cfNOGO than irNOGO trials. These results seem to suggest that the older adults recruited more control processes in order to conquer the commitment of responses in the no-go trials, especially in the irNOGO trials. This age-related compensatory response of recruiting more control processes was specifically seen in the 20% no-go trial probability condition. This study therefore provides a deeper understanding into how older adults adopt strategies for performing the go/no-go task such as devoting more control processes to inhibiting the irNOGO trials compared to the cfNOGO trials in order to cope with their deficient inhibition ability.